DEVELOPMENT OF THE SYSTEM OF EXTERNAL PROVISION OF HIGHER EDUCATION IN UKRAINE: THE PAST, TODAY AND THE FUTURE - Loza, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article presents the development of the system of external quality assurance of higher education in Ukraine. In particular, the positive and negative tendencies of the formation of the external security system in the post-Soviet period are considered, the situation of the present proceeding from the analysis of the Laws of Ukraine “On Higher Education” 2014 is outlined and "On Education" 2017, as well as the ways and prospects for its further transformation.In the first decade of Ukraine's independence, there has been a decline in the quality of higher education. The education management system of this period was, in fact, a Soviet model adapted to the needs of the transition period. Attempts by the state to further establish an effective institution of state accreditation of higher education institutions for a number of objective reasons (state monopoly on the decision of the conditions of accreditation of higher education institutions, non-competitiveness, opacity and non-accountability of the accreditation mechanism, corruption) revealed its inefficiency. The main trend in the higher education system of the late 1990s and early 2000s was the quantitative growth of higher education institutions, which was accompanied by a decrease in the quality of education and a significant imbalance of graduates' specializations to the needs of the labor market. Obvious losses were suffered by such advantages of Ukrainian education as fundamentality, systematic and practical orientation.The first steps aimed at improving the external quality assurance system of higher education was the Bologna Process, to which Ukraine joined in 2005, committing itself to make appropriate changes to the national education system and to join the work on setting priorities in the process of creating a single European Higher Education Area. The next key round of positive changes and integration processes in the European Union in the higher education system was the adoption of the Law of Ukraine "On Higher Education" of July 1, 2014, in which one of the important innovations was the creation of a National Agency for Quality Assurance in Higher Education and an attempt to legitimize the idea of independent institutions of assessment and quality assurance of education. The Law on Education, adopted on September 5, 2017, provided new opportunities for the development and enhancement of its competitiveness for education seekers, educators and educational institutions. The law has substantially distributed the powers and areas of responsibility of the authorities in education, significantly expanded the public's right to participate in the management and control of the activities of educational institutions and authorities, etc. The strategy of development of civic education for the period up to 2022 aims to form a holistic system of education, to create appropriate conditions for the functioning of the education system, implementation of the system of monitoring the quality of education and assessment of civic competences.The above points to the future positive changes in the creation of an effective system of external quality assurance of higher education aimed at joining the European educational, scientific and professional space.
Keywords: quality of higher education, external security system, Law of Ukraine “On Higher Education”